High-performance asphalt mixture based on high and low temperature service environment and preparation method thereof

By rationally preparing asphalt aggregate and basalt fibers in asphalt mixture, the contradiction between high temperature, low temperature and water stability in the prior art is solved, the overall performance of asphalt mixture is improved, and the asphalt pavement is extended Service life and improved throughput.

CN119285275APending Publication Date: 2025-01-10CHINA RAILWAY 16TH BUREAU GRP ROAD & BRIDGE ENG CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411385138.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

There are contradictions in the existing asphalt mixture in terms of high temperature stability, low temperature crack resistance, water stability and durability, and it is difficult to meet the actual road environment needs at the same time. Especially after the increase of freight vehicles, it leads to serious ruts, which reduces the transportation of highways. Efficiency and service quality.

Method used

High-performance asphalt mixtures in high and low-temperature service environments, including asphalt aggregates and basalt fiber additives, the aggregate volume accounts for 95-96%, the asphalt volume accounts for 4-5%, and the fiber additive volume percentage is 0.15-0.30%. Reasonable aggregate grading and fiber ratio optimization to improve the high-temperature, low-temperature and water stability of asphalt mixture.

Benefits of technology

The high-temperature stability, low-temperature bending resistance, water stability and durability of asphalt mixture are achieved, extending the service life of asphalt pavement, and enhancing the passing capacity and pavement performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005070817130000051
    Figure BDA0005070817130000051
  • Figure BDA0005070817130000052
    Figure BDA0005070817130000052
  • Figure BDA0005070817130000061
    Figure BDA0005070817130000061
Patent Text Reader

Abstract

The invention relates to the field of asphalt mixture preparation of road engineering, and discloses a high-performance asphalt mixture based on high and low temperature service environments and a preparation method thereof. According to the asphalt mixture disclosed by the invention, aggregate is used as a main material, a small amount of proper asphalt and fibers are added as auxiliary materials, and the aggregate structure of the asphalt mixture is properly selected, so that the grading structure of coarse and fine aggregate is more reasonable, and the coarse and fine aggregate of the asphalt mixture is embedded better, so that the volume index of the asphalt mixture can be better obtained; according to the preparation method, the proper porosity is particularly ensured, so that the high temperature, low temperature and water stability of the asphalt mixture can be optimized, the defects of the existing asphalt mixture preparation technology are overcome, and particularly the defects of the asphalt mixture mix proportion design based on a complex service temperature environment are overcome. The asphalt mixture can adapt to more complex road use environments, has good durability, and is suitable for asphalt mixture surface layers of highway road engineering, municipal road engineering and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of asphalt mixture preparation for road engineering, and in particular to a high-performance asphalt mixture under high and low temperature service environments and a preparation method thereof. Background Art

[0002] Road projects, especially highways, usually use asphalt pavement as the surface layer of the road. Due to the long-term direct impact of vehicle loads and high and low temperature service environment factors, the road surface will have rutting, cracks, potholes, subsidence, looseness, congestion, oil spillage and other problems, which directly affect the safety and service life of the asphalt pavement, resulting in the actual service life of the pavement far less than the service life in the design stage, and the asphalt pavement cannot play its superiority over concrete pavement. In particular, due to the substantial increase in freight vehicles, the road surface has more rutting and serious damage. This typical disease problem has greatly reduced the transportation efficiency and service quality of the highway. For this reason, it is particularly important to study how to improve the road performance of asphalt mixtures, such as high temperature stability, low temperature bending and tensile strength, water stability, durability and anti-skid safety, and adopt measures to enhance the traffic capacity and service life of asphalt pavements.

[0003] The gradation and type of asphalt mixture mineral aggregates widely used now are mainly designed by (AC, SMA) design methods. In terms of high temperature stability, low temperature crack resistance, skid resistance, durability, fatigue performance, etc., they are often contradictory or mutually restrictive. Taking care of one performance is likely to reduce the performance of the other. This leads to how to design an asphalt mixture design method that more realistically simulates actual road conditions, so that the force of the asphalt mixture is more in line with the actual road use environment and process, which is currently a top priority. Summary of the invention

[0004] In view of this, the purpose of the present application is to provide a high-performance asphalt mixture and a preparation method thereof based on high and low temperature service environments, so that the asphalt mixture has high high temperature performance, low temperature performance and water stability at the same time.

[0005] In order to solve the above-mentioned technical problems / achieve the above-mentioned purposes or at least partially solve the above-mentioned technical problems / achieve the above-mentioned purposes, as the first aspect of the present application, a high-performance asphalt mixture based on high and low temperature service environments is provided, including asphalt aggregate and fiber additives; the asphalt aggregate includes asphalt and aggregate, wherein the volume percentage of the aggregate is 95-96%, and the volume percentage of the asphalt is 4-5%; the volume percentage of the fiber additive is 0.15-0.30% of the volume of the asphalt aggregate.

[0006] Optionally, the gradation range of the aggregate is as follows:

[0007] 19mm corresponds to a quality pass rate of 100%;

[0008] 13.2mm corresponds to a quality pass rate of 95-100%;

[0009] 9.5mm corresponds to a quality pass rate of 78-80%;

[0010] 4.75mm corresponds to a quality pass rate of 54-56%;

[0011] 2.36mm corresponds to a quality pass rate of 28-29%;

[0012] 1.18mm corresponds to a quality pass rate of 19-21%;

[0013] 0.6mm corresponds to a quality pass rate of 16-17%;

[0014] 0.3mm corresponds to a quality pass rate of 13-15%;

[0015] 0.15mm corresponds to a quality pass rate of 12-14%;

[0016] The corresponding quality pass rate of 0.075mm is 3.2-4%.

[0017] Further optionally, the aggregate includes coarse aggregate, fine aggregate and mineral powder, the coarse aggregate and fine aggregate include basalt aggregate, and the mineral powder includes limestone mineral powder. Further optionally, the basalt coarse aggregate is selected from aggregates with a particle size of 3 to 16 mm, the basalt fine aggregate is selected from aggregates with a particle size of 0 to 3 mm, and the mineral powder is selected from limestone mineral powder with a particle size of less than 0.075 mm.

[0018] Optionally, the fiber additive is selected from basalt fiber, with a length of 6±1.5 mm, a breaking strength of ≥2000 MPa, and an elongation at break of ≥2.5%.

[0019] Optionally, after the asphalt mixture is compacted, the aggregate void ratio is 14.18-14.21%, the asphalt filling ratio is 71.77-77.82%, and the powder-rubber ratio is 0.82-0.83.

[0020] Optionally, the asphalt is selected from SBS modified petroleum asphalt.

[0021] Optionally, after the asphalt mixture is compacted, the void ratio is 3.9-4.1%.

[0022] As a second aspect of the present application, a method for preparing the asphalt mixture is provided, comprising:

[0023] After the asphalt is heated, it is added to the preheated aggregate that has been stirred evenly and the stirring is continued. Then, the preheated fiber additive is added and stirred evenly to obtain the asphalt mixture.

[0024] The asphalt mixture of the present application is mainly composed of aggregates, with a small amount of suitable asphalt and fiber added as an auxiliary. Combined with the appropriate selection of the aggregate structure of the asphalt mixture, the gradation structure of coarse and fine aggregates is more reasonable, and the inlay between the coarse and fine aggregates of the asphalt mixture is better, so that it can better have the volume indicators of the asphalt mixture, especially ensuring the appropriate void ratio, so that the high temperature, low temperature and water stability of the asphalt mixture can be optimized, overcoming the shortcomings of the existing asphalt mixture preparation technology, especially the shortcomings of the asphalt mixture mix design based on complex service temperature environments, so that the asphalt mixture can adapt to more complex road use environments, has good durability, and is suitable for asphalt mixture surface layers of highway road projects, municipal road projects, etc. DETAILED DESCRIPTION

[0025] The present application discloses a high-performance asphalt mixture and its preparation method based on high and low temperature service environments. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The products, processes and applications described in this application have been described through preferred embodiments. Relevant personnel can obviously modify or appropriately change and combine the products, processes and applications described in this article without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0026] It should be noted that, in this article, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.

[0027] The asphalt mixture provided in the present application is a high-performance asphalt mixture based on high and low temperature service environments. The asphalt dosage and void ratio of the asphalt mixture are in an optimal ratio, especially its interaction with the set graded aggregate, coupled with the use of basalt fiber, so that the bonding effect between the above aggregate and asphalt is better, and the recommended volume percentage of basalt fiber is positively correlated to the performance improvement of the asphalt mixture. Too much or too little will reduce the performance of the asphalt mixture; the mixing ratio of the entire asphalt mixture improves the overall density and stability of the asphalt mixture, and improves the road performance of the asphalt mixture, such as high temperature stability, low temperature flexural tensile strength, water stability, durability and anti-skid safety, etc., and thereby enhances the traffic capacity and service life of the asphalt pavement, so that the asphalt pavement can have good road performance under different temperature environments.

[0028] In the first aspect of the present application, a high-performance asphalt mixture based on high and low temperature service environments is provided, including asphalt aggregate and fiber additives; the asphalt aggregate includes asphalt and aggregate, wherein the volume proportion of the aggregate is 95-96%, and the volume proportion of the asphalt is 4-5%; the volume percentage of the fiber additive is 0.15-0.30% of the volume of the asphalt aggregate.

[0029] In certain embodiments of the present application, the gradation range of the aggregate is as follows:

[0030] 19mm corresponds to a quality pass rate of 100%;

[0031] 13.2mm corresponds to a quality pass rate of 95-100%;

[0032] 9.5mm corresponds to a quality pass rate of 78-80%;

[0033] 4.75mm corresponds to a quality pass rate of 54-56%;

[0034] 2.36mm corresponds to a quality pass rate of 28-29%;

[0035] 1.18mm corresponds to a quality pass rate of 19-21%;

[0036] 0.6mm corresponds to a quality pass rate of 16-17%;

[0037] 0.3mm corresponds to a quality pass rate of 13-15%;

[0038] 0.15mm corresponds to a quality pass rate of 12-14%;

[0039] The corresponding quality pass rate of 0.075mm is 3.2-4%.

[0040] The overall gradation design of the present application is relatively coarse, the large-size sieve hole pass rate is generally high, and the small-size sieve hole pass rate is relatively low. This design idea can make the asphalt mixture more solid, and it is obviously helpful to improve the high temperature stability and low temperature crack resistance. In some other embodiments of the present application, the gradation range of the aggregate is as follows:

[0041] 19mm corresponds to a quality pass rate of 100%

[0042] 13.2mm corresponds to a quality pass rate of 95.51%;

[0043] 9.5mm corresponds to a quality pass rate of 78.16%;

[0044] 4.75mm corresponds to a quality pass rate of 55.03%;

[0045] 2.36mm corresponds to a quality pass rate of 28.15%;

[0046] 1.18mm corresponds to a quality pass rate of 19.97%;

[0047] 0.6mm corresponds to a quality pass rate of 16.63%;

[0048] 0.3mm corresponds to a quality pass rate of 14.21%;

[0049] 0.15mm corresponds to a quality pass rate of 12.92%;

[0050] The corresponding quality pass rate of 0.075mm is 3.81%.

[0051] In certain embodiments of the present application, the aggregate includes coarse aggregate, fine aggregate and mineral powder. The coarse aggregate and fine aggregate are both basalt aggregates. Basalt aggregates have higher strength and are harder, and are more suitable for high-performance asphalt mixtures with a nominal maximum size of 13 mm. The basalt coarse aggregate is selected from aggregates with a particle size of 3 to 16 mm, the basalt fine aggregate is selected from aggregates with a particle size of 0 to 3 mm, and the mineral powder is selected from limestone mineral powder, and further selected from limestone mineral powder with a particle size of less than 0.075 mm, which can make the asphalt and the aggregate better bonded; in other embodiments of the present application, the basalt coarse aggregate is selected from three particle size specifications of 3 to 5 mm, 5 to 10 mm and 10 to 16 mm respectively;

[0052] In certain embodiments of the present application, the mass proportions of each aggregate in the total aggregate are: coarse aggregate 71%, fine aggregate 21%, and mineral powder 8%; among the coarse aggregate, the particle size of 10-16 mm accounts for 26%, the particle size of 5-10 mm accounts for 25%, and the particle size of 3-5 mm accounts for 20%.

[0053] In certain embodiments of the present application, the fiber is selected from basalt fiber, more specifically, basalt chopped fiber, with a length of 6±1.5 mm, a breaking strength of ≥2000 MPa, and an elongation at break of ≥2.5%.

[0054] In some embodiments of the present application, after the asphalt mixture is compacted, the aggregate gap ratio is 14.18-14.21%, the asphalt filling ratio is 71.77-77.82%, and the powder-rubber ratio is 0.82-0.83. In some other embodiments of the present application, after the asphalt mixture is compacted, the void ratio is 3.9-4.1%.

[0055] In certain embodiments of the present application, the asphalt is selected from SBS modified petroleum asphalt, such as ID grade SBS modified asphalt. SBS modified asphalt is based on base asphalt and a certain proportion of SBS modifier is added. It belongs to elastic plastic modified asphalt and its grade is PG70-10.

[0056] In a second aspect of the present application, a method for preparing the asphalt mixture is provided, comprising:

[0057] After the asphalt is heated, it is added to the preheated aggregate that has been stirred evenly and the stirring is continued. Then, the preheated fiber is added and stirred evenly to obtain the asphalt mixture.

[0058] In this application, the asphalt mixture provided meets the following performance index requirements: the high temperature performance index dynamic stability value is not less than 7200 times / mm; the water stability index Marshall stability is not less than 11.2KN, the Marshall conventional flow value is not less than 2.55mm, the Marshall immersion stability is not less than 9.73KN, the Marshall immersion flow value is not less than 3.22mm, and the Marshall immersion residual stability is not less than 89.6%; the low temperature performance index splitting tensile strength ratio is not less than 83%, the flexural tensile strength is not less than 10.99MPa, the maximum flexural tensile strain is not less than 4100με, and the bending stiffness modulus is not greater than 2700MPa. The asphalt mixture described in this application is most prominent in high temperature performance indicators, and on this basis, it ensures that the water stability and low temperature performance are also good, and can take into account multiple performance indicators at a high level at the same time.

[0059] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.

[0060] The following is a further description of a high-performance asphalt mixture and a preparation method thereof provided in this application under high and low temperature service environments.

[0061] Embodiment 1:

[0062] 1. Raw materials

[0063] Basalt: Commercially available basalt, technical indicators are shown in Table 1 and Table 2.

[0064] Mineral powder: commercially available limestone mineral powder, the technical indicators are shown in Table 3.

[0065] Asphalt: The ID grade SBS modified asphalt on the market is PG70-10. The relevant technical indicators of asphalt are tested according to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering". The technical indicators are shown in Table 4.

[0066] Fiber: Basalt chopped fibers are used. The fibers are clean and smooth, meeting the requirements of "Fibers for Asphalt Pavement". The technical indicators are shown in Table 5.

[0067] Table 1 Technical indicators of basalt coarse aggregate

[0068]

[0069] Table 2 Technical indicators of fine aggregate

[0070]

[0071]

[0072] Table 3 Technical indicators of mineral powder

[0073]

[0074] Table 4 Technical indicators of SBS modified asphalt

[0075]

[0076] Table 5 Physical and technical indicators of chopped basalt fiber

[0077]

[0078] 2. Mix ratio design

[0079] The proportion of each aggregate in the total aggregate is shown in Table 6, and the quality pass rate of each aggregate is shown in Table 7;

[0080] Table 6 The mass ratio of each aggregate in the embodiment to the total aggregate

[0081]

[0082] Table 7 The quality pass rate of each aggregate in the embodiment

[0083]

[0084] 3. Preparation process

[0085] The above-mentioned material is used, after the asphalt is heated, it is added to the preheated aggregate that is stirred evenly and continues to be stirred, and then the preheated basalt fiber is added and stirred evenly to obtain the asphalt mixture.

[0086] The number of gyratory compaction is determined according to the traffic volume level. Superpave not only has corresponding constraints on the PG classification of the binder for different cumulative equivalent axle load times (ESALS), but also stipulates the number of gyratory compaction. The ESALS designed in this application is 3~30×10 6 , which belongs to medium to heavy traffic. The Superpave design gyratory compaction times are shown in Table 8, and the gyratory compaction data of asphalt mixture when the asphalt volume content is 4.48% are shown in Table 9;

[0087] Table 8 Superpave design rotation compaction times

[0088]

[0089] Table 9 Gyratory compaction data of asphalt mixture when the asphalt volume content is 4.48%

[0090]

[0091]

[0092] After compaction, the aggregate gap ratio is 14.18-14.21%, the asphalt filling ratio is 71.77-77.82%, the powder-rubber ratio is 0.82-0.83, and the void ratio is 3.9-4.1%.

[0093] 4. Best formula

[0094] Table 10 Optimal mix ratio of asphalt mixture design (maximum nominal size is 13 mm, volume ratio)

[0095]

[0096] The volume percentage of basalt fiber is 0.30% of the total volume of asphalt aggregate.

[0097] Embodiment 2:

[0098] Refer to the process of Example 1, except that the amount of asphalt used is 4.4%.

[0099] Comparative Example 1:

[0100] Refer to the process of Example 1, the difference is that the volume proportion of basalt fiber is 0.45% of the total volume of asphalt aggregate, that is, the proportion of basalt fiber relative to the total volume of asphalt aggregate is increased, and the rest is consistent with Example 1.

[0101] Comparative Example 2:

[0102] Refer to the process of Example 1, the difference is that the volume proportion of asphalt is 3.0%, that is, the proportion of asphalt in the asphalt aggregate is reduced, and the rest is consistent with Example 1.

[0103] Comparative Example 3:

[0104] Refer to the process of Example 1, except that the gradation of aggregate is adjusted as shown in Table 11 and Table 12:

[0105] Table 11

[0106]

[0107] Table 12

[0108]

[0109] Comparative Example 4:

[0110] Refer to the process of Example 1, except that the gradation of aggregate is adjusted as shown in Table 13 and Table 14:

[0111] Table 13

[0112]

[0113] Table 14

[0114]

[0115] Experimental example:

[0116] (1) Road performance testing

[0117] Example 1 and Comparative Example 1 and Comparative Example 2 were subjected to rutting test, Marshall test, immersion Marshall test, freeze-thaw splitting test and beam bending test, and the results are shown in Tables 15 to 17 respectively; Table 15 Test performance parameter values ​​of asphalt mixture of Example 1 (asphalt content 4.48%, basalt fiber content 0.30%)

[0118]

[0119] Note: The smaller the bending stiffness modulus, the better the bending tensile performance, the same below;

[0120] Table 16 Test performance parameter values ​​of asphalt mixture in comparative example 1

[0121]

[0122] Table 17 Test performance parameter values ​​of high performance asphalt mixture in comparative example 2

[0123]

[0124]

[0125] The dynamic stability index of the rutting test is used to measure high temperature performance, the Marshall test index is used to measure water stability, that is, to measure whether good performance can be achieved in rainy weather, and the freeze-thaw splitting test and beam bending test index are used to measure low temperature performance.

[0126] It can be clearly seen from the experimental results in Tables 15 to 17 that the dynamic stability of the asphalt mixture of the present application is as high as 7270.09 (times / mm), while the two comparative examples are 6302.90 (times / mm) and 5464.15 (times / mm), respectively. The difference is very significant, indicating that the asphalt mixture of the present application has excellent high temperature performance when used in road engineering;

[0127] Among the various indicators of the Marshall test, compared with Comparative Example 1 and Comparative Example 2, the asphalt mixture of the present application is superior in Marshall stability, Marshall conventional flow value, Marshall water immersion stability, Marshall water immersion flow value, and Marshall water immersion residual stability, which indicates that it has higher stability even in rainy weather environments;

[0128] The results of the freeze-thaw splitting test and the beam bending test also show intuitively that the splitting tensile strength and flexural tensile strength of the asphalt mixture of the present application are relatively high, indicating the superior low-temperature performance.

[0129] (2) Estimated volumetric properties of asphalt mixture

[0130] Before determining the optimal ratio in Example 1, the present application used Example 2 and Comparative Example 3 and Comparative Example 4 to test the estimated volume characteristics of asphalt mixtures with different aggregate gradations, and the results are shown in Table 18 below;

[0131] Table 18

[0132]

[0133] The powder-to-binder ratio is a very important criterion. Under the same asphalt dosage, the powder-to-binder ratio of Example 2 of the present application is in an appropriate range, and the powder-to-binder ratio of Comparative Example 3 is low, indicating that the asphalt mixture is internally unstable and too viscous, resulting in inability to be used normally; the powder-to-binder ratio of Comparative Example 4 is high, indicating that the asphalt mixture is not durable enough and is loose as a whole and cannot be formed. Therefore, the subsequent experiments did not continue to use the schemes of Comparative Examples 3 and 4. The above results show that the adjustment of aggregate gradation will affect the pavement performance of the asphalt mixture, and only the appropriate gradation range can achieve better pavement performance.

[0134] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A high-performance asphalt mixture based on high and low temperature service environment, characterized in that: It comprises asphalt aggregate and fiber additive; the asphalt aggregate comprises asphalt and aggregate, wherein the volume proportion of the aggregate is 95-96%, and the volume proportion of the asphalt is 4-5%; the volume percentage of the fiber additive is 0.15-0.30% of the volume of the asphalt aggregate.

2. The asphalt mixture according to claim 1, characterized in that: The gradation range of the aggregate is as follows: The corresponding quality pass rate of 19mm is 100%; the corresponding quality pass rate of 13.2mm is 95-100%; the corresponding quality pass rate of 9.5mm is 78-80%; the corresponding quality pass rate of 4.75mm is 54-56%; the corresponding quality pass rate of 2.36mm is 28-29%; the corresponding quality pass rate of 1.18mm is 19-21%; The corresponding quality pass rate of 0.6mm is 16-17%; the corresponding quality pass rate of 0.3mm is 13-15%; the corresponding quality pass rate of 0.15mm is 12-14%; and the corresponding quality pass rate of 0.075mm is 3.2-4%.

3. The asphalt mixture according to claim 1 or 2, characterized in that: The aggregate comprises coarse aggregate, fine aggregate and mineral powder, the coarse aggregate and fine aggregate comprise basalt aggregate, and the mineral powder comprises limestone mineral powder.

4. The asphalt mixture according to claim 3, characterized in that: The basalt coarse aggregate is selected from aggregates with a particle size of 3 to 16 mm, the basalt fine aggregate is selected from aggregates with a particle size of 0 to 3 mm, and the mineral powder is selected from limestone mineral powder with a particle size of less than 0.075 mm.

5. The asphalt mixture according to claim 1, characterized in that: The fiber additive is selected from basalt fiber, with a length of 6±1.5 mm, a breaking strength of ≥2000 MPa, and a breaking elongation of ≥2.5%.

6. The asphalt mixture according to claim 1, characterized in that: After the asphalt mixture is compacted, the aggregate gap ratio is 14.18-14.21%, the asphalt filling ratio is 71.77-77.82%, and the powder-rubber ratio is 0.82-0.

83.

7. The asphalt mixture according to claim 1, characterized in that: The asphalt is selected from SBS modified petroleum asphalt.

8. The asphalt mixture according to claim 1, characterized in that: After the asphalt mixture is compacted, the void ratio is 3.9-4.1%.

9. The method for preparing asphalt mixture according to claim 1, characterized in that: include: After the asphalt is heated, it is added to the preheated aggregate that has been stirred evenly and the stirring is continued. Then, the preheated fiber is added and stirred evenly to obtain the asphalt mixture.